Alopecia in Multiple Sclerosis Patients Treated with Disease Modifying Therapies. (23rd June 2022) - Porwal, Mokshal H.; Salter, Amber; Patel, Dhruvkumar; Obeidat, Ahmed Z.
BACKGROUND: There is currently limited literature addressing the reporting of alopecia in multiple sclerosis (MS) patients treated with disease-modifying therapies (DMTs). Anecdotal reports of hair thinning from patients on various DMTs prompted further investigation of a large database. OBJECTIVE: To analyze total reports, source of reporting, age distribution, and sex distribution of alopecia associated with DMTs. METHODS: FDA Adverse Event Reporting System (FAERS) public dashboard and OpenFDA database were analyzed for alopecia reports between January 1, 2009, and June 30, 2020, attributed to usage in MS of FDA approved DMTs. The main outcomes included total reports for each drug, age, sex distribution, and reporting source. OpenFDA data was used for statistical analyses including reporting odds ratios (ROR) and information components. RESULTS: 8759 alopecia reports were identified among 44 114 adverse events in skin and subcutaneous tissue disorders (19.9%). 3701 (42.3%) with teriflunomide, 1675 (19.1%) with dimethyl fumarate, 985 (11.2%) with natalizumab, 926 (10.6%) with fingolimod, 659 (7.5%) with interferon beta-1a, 257 (2.9%) with glatiramer acetate, 243 (2.8%) with ocrelizumab, 124 (1.4%) with interferon beta-1b, 117 (1.3%) with alemtuzumab, 36 (.4%) with siponimod, 24 (.3%) with cladribine, and 12 (.1%) with rituximab. Reports were mostly made by patients (78.3%) and highest in fifth and sixth decades of life. OpenFDA analyses showed increased ROR (ROR 95% confidence interval) of alopecia in females with teriflunomide (18.00, 17.12-18.93), alemtuzumab (1.43, 1.16-1.76), dimethyl fumarate (1.26, 1.18-1.34), and ocrelizumab (1.28, 1.11-1.49). Increased ROR in males was associated with teriflunomide (24.65, 20.72-29.31). CONCLUSION: We identified many reports of alopecia for DMTs in addition to teriflunomide. Within the limitations of the database, increased RORs of alopecia were observed for females treated with alemtuzumab, dimethyl fumarate, and ocrelizumab. The source of reporting was largely driven by female patients. Possible alopecia, even if transient, should be considered during patient education when starting DMTs.